The Impact of Combination of Human Capital and Financial Literacy in Encouraging Economic Growth in Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The main objective of this study is to investigate the role of financial literacy and human capital development on economic growth in Indonesia. This study uses econometrics to investigate the role of financial literacy and human capital development on economic growth in Indonesia. This research is complementary to previous research with a neutral position from previous research which has pro and con conclusions regarding the role of finance and human capital on economic growth, especially in developing countries such as Indonesia. We found that Financial literacy in Indonesia not only provides a direct impetus to economic growth but also provides impetus or strengthens the influence of human capital in providing impetus to economic growth. However, human capital cannot be said to strengthen the influence of financial literacy in encouraging economic growth because in estimating the influence of human capital in strengthening financial literacy in providing encouragement to economic growth, the positive effect is not significant. Human capital has a significant positive effect on economic growth. So that the combination of financial literacy and human capital can be a good combination in providing a boost to economic growth.